Protective effect of hydroxychloroquine on rheumatoid arthritis‐associated atherosclerosis. Issue 2 (19th April 2019) - Shi, Na; Zhang, Shuangyue; Silverman, Gregg; Li, Mengtao; Cai, Jun; Niu, Haitao
Abstract: Background: Patients with rheumatoid arthritis (RA) have an increased risk for cardiovascular disease. We examined the effect of gut microbiota in a mouse model of RA that develops atherosclerosis. Methods: We created three groups of K/BxN female mice that were positive for the anti‐glucose‐6‐phosphate isomerase (GPI) antibody: control diet (CD), high fat diet (HFD), and HFD with hydroxychloroquine (HFD + HCQ). Serological tests were used to detect the serum levels of total cholesterol (TCHO), low‐density lipoprotein cholesterol (LDL‐C), triglyceride (TG), high‐density lipoprotein cholesterol (HDL‐C), anti‐GPI antibody titers, and serum cytokines. Atherosclerotic plaque was determined by histological analysis, and gut microbiota were determined by 16sV4 sequencing. Results: Relative to mice given the CD, those receiving the HFD had increased serum levels of LDL‐C, TCHO, and TG, decreased serum levels of HDL‐C, increased atherosclerotic lesions in the aortic root, and altered gut microbiota. Addition of HCQ to HFD decreased the serum levels of LDL‐C, TCHO, and TG, increased serum levels of HDL‐C, and decreased the atherosclerotic lesions in the aortic root. Mice receiving HFD + HCQ also had the greatest bacterial diversity among the three experimental groups. Moreover, HCQ treatment significantly increased the abundance of Akkermansia and Parabacteroides, and decreased the abundance of Clostridium sensu stricto cluster 1, and therefore may be responsible for the reduced RA‐associated atherosclerosis and dyslipidemia. Conclusion: Our mouse model of RA indicated that HFD increased ankle width and aggravated atherosclerosis and dyslipidemia, and that HCQ alleviated the dyslipidemia and atherosclerosis, but had no effect on ankle width.